Health Disparities Among African Americans - E. Kelly Sanford; Josie Scales; Essame Hamido; Waldine DeBerry (European Scientific Journal, ESJ, 2017)
The purpose of this research, “Health Disparities among African Americans,” is to increase our understanding of the demographic differences of health disparities that exist in America. The state of Tennessee is ranked third in the nation for obesity, and 48th in the nation in education success (CDC, 2014). The correlation between these variables, along with the intervening variable of culture, suggests a strong impact on poor health and wellness among African Americans. This research suggeststhe peculiar nature of prejudice and its relationship to poor health, race, gender, social economic status and culture as it relates to precursors of poor health. This research assessed 300 TSU African American students on the comparative analysis of body weight and body muscle (BMI Ratio) to the national average of BMI Ratios for teens to young adults ranging in age from 17-20. Comparative analysis suggests that the participants were above the national BMI average. Active Learning Workshop was useful in helping participants to increase their understanding of the correlation between weight and health and wellness.